Technical and tactical performance indicators determining successful and unsuccessful team in elite beach soccer - Rabiu Muazu, Musa; Anwar, P. P. Abdul Majeed; Norlaila Azura, Kosni; Mohamad Razali, Abdullah (Springer, 2020)
The success of a given elite beach soccer team is identified through a number of technical and tactical performance indicators in this chapter. The demarcation of the winning and losing team was determined through the use of the Louvain clustering technique. Subsequently, a number of artificial neural network (ANN) models were developed by varying different hyperparameters in evaluating its ability to accurately ascertaining the class of a team. It was shown from the study that through the framework provided, the best ANN architecture, as well as performance indicators identified, could yield an average classification accuracy of 92.5% on the validation and test dataset.